Genome‐wide association study in musician's dystonia: A risk variant at the arylsulfatase G locus?. Issue 7 (26th December 2013) - Lohmann, Katja; Schmidt, Alexander; Schillert, Arne; Winkler, Susen; Albanese, Alberto; Baas, Frank; Bentivoglio, Anna Rita; Borngräber, Friederike; Brüggemann, Norbert; Defazio, Giovanni; Del Sorbo, Francesca; Deuschl, Günther; et al.
ABSTRACT Musician's dystonia (MD) affects 1% to 2% of professional musicians and frequently terminates performance careers. It is characterized by loss of voluntary motor control when playing the instrument. Little is known about genetic risk factors, although MD or writer's dystonia (WD) occurs in relatives of 20% of MD patients. We conducted a 2‐stage genome‐wide association study in whites. Genotypes at 557, 620 single‐nucleotide polymorphisms (SNPs) passed stringent quality control for 127 patients and 984 controls. Ten SNPs revealed P < 10−5 and entered the replication phase including 116 MD patients and 125 healthy musicians. A genome‐wide significant SNP (P < 5 × 10−8) was also genotyped in 208 German or Dutch WD patients, 1, 969 Caucasian, Spanish, and Japanese patients with other forms of focal or segmental dystonia as well as in 2, 233 ethnically matched controls. Genome‐wide significance with MD was observed for an intronic variant in the arylsulfatase G (ARSG) gene (rs11655081; P = 3.95 × 10−9; odds ratio [OR], 4.33; 95% confidence interval [CI], 2.66‐7.05). rs11655081 was also associated with WD (P = 2.78 × 10−2) but not with any other focal or segmental dystonia. The allele frequency of rs11655081 varies substantially between different populations. The population stratification in our sample was modest (λ = 1.07), but the effect size may be overestimated. Using a small but homogenous patient sample, we provide data for a possible association of ARSG with MD. The variant may also contribute to the risk of WD, a form of dystonia that is often found in relatives of MD patients. © 2013 International Parkinson and Movement Disorder Society